Politics Ethics and Civil Society Studies: A Systematic Literature Review (SLR) - Erdawanti, Dilla Tri (Internasional Journal of Politics and Public Policy, 2025)
This research aims to explain the crucial role of civil society in a country because it plays an important role in overseeing policy making. In line with that, the government is also considered to have a vital role in ensuring the welfare of its citizens on the basis of established policies. The research method applied in this study was a systematic literature review which used 94 scientific articles sourced from the Scopus database. Review articles using the Vosviewer application. The research results show that political ethics and civil society are closely related, where political ethics is the basis for the government in managing political issues properly, while civil society helps monitor and ensure the implementation of the concept of political ethics. This research emphasizes the importance of understanding the relationship between political ethics and civil society in the context of developing and maintaining a just, democratic and sustainable state. The results of this research contribute to the development of a research roadmap on politics ethics and civil society. The limitation of this research is that the articles used only come from the Scopus database so that the research findings cannot comprehensively describe the issue of politics, ethics and civil society.